2017
DOI: 10.1097/acm.0000000000001871
|View full text |Cite
|
Sign up to set email alerts
|

Mediators of Racial/Ethnic Disparities in Mentored K Award Receipt Among U.S. Medical School Graduates

Abstract: Purpose Mentored K (K01/K08/K23) career development awards are positively associated with physicians’ success as independent investigators; however, individuals in some racial/ethnic groups are less likely than others to receive this federal funding. The authors sought to identify variables that can explain (mediate) the association between race/ethnicity and mentored K award receipt among U.S. LCME-accredited medical school graduates who planned research-related careers. Method The authors analyzed de-ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 25 publications
3
18
0
Order By: Relevance
“…(31) Using mediation analysis,(34) Step 1 scores alone explained 80% of the effect of race/ethnicity on K-award receipt among medical-school graduates planning research-related careers. (35) Thus, racial/ethnic differences in medical-school academic performance may contribute to persistent racial/ethnic disparities in physicians’ participation in the federally funded biomedical-research workforce at multiple stages of their post-graduation professional development.…”
Section: Discussionmentioning
confidence: 99%
“…(31) Using mediation analysis,(34) Step 1 scores alone explained 80% of the effect of race/ethnicity on K-award receipt among medical-school graduates planning research-related careers. (35) Thus, racial/ethnic differences in medical-school academic performance may contribute to persistent racial/ethnic disparities in physicians’ participation in the federally funded biomedical-research workforce at multiple stages of their post-graduation professional development.…”
Section: Discussionmentioning
confidence: 99%
“…Research experience, paper authorship, and F32 awards are predictors of successful mentored K award applications, and this association is particularly strong for UIM groups ( 37 ). However, high-quality mentorship for developing physician-scientists who will persist beyond the early stages in academia is of vital importance.…”
Section: Opportunities To Enhance Sustainability Of the Pulmonary Crmentioning
confidence: 99%
“…Several studies have revealed disparities in US medical student performances on the USMLE, with UIM students disproportionately scoring lower on USMLE step 1 and step 2 exams when compared with students who do not identify as UIM 4,5,9,11,12 (Table 2). Similar disparities in examination performance exist for the Medical College Admission Test.…”
Section: Usmle Scoresmentioning
confidence: 99%
“…Nonpathology studies have suggested that using objective academic metrics in isolation (ie, United States Medical Licensing Examination [USMLE] step 1 and step 2 scores, medical school clerkship grades and evaluations, Alpha Omega Alpha Honor Medical Society [AOA] status, and research experiences) as initial residency interview screening tools may disproportionately screen out UIM applicants. [5][6][7][8][9][10][11][12][13] Other studies have shown that implicit biases may have a negative impact on residency applicant selection. [14][15][16][17][18][19][20] Nonetheless, the benefits of diversity in training programs are well described in the literature and include protection against depression for interns from both UIM and non-UIM groups and promotion of a more diverse training experience.…”
mentioning
confidence: 99%